ISOLASI DAN IDENTIFIKASI KAPANG SELULOLITIK DARI KULIT ARI KEDELAI LIMBAH PENGOLAHAN SUSU KEDELAI - ESPE SIMANJUNTAK; EVY ROSSI; USMAN PATO (Jurnal Sagu, 2017)
The aim of this research was to isolate and to identify the genus selulolitic mold from the husk soybean wasteof soybean milk processing industry. This research was conducted using two phase experiments, the firstphase was to isolate mold from the husk soybean and the second phase was to identify the isolated seluloliticmold. Data were tabulated and analyzed descriptively. The results showed that of 22 isolates were isolated,only 16 isolates were declared as mold. Out of 16 isolates, seven isolates were able to produce a clear zoneat CMC media indicating that isolates produce enzymes selulose. Among seven isolates, four isolates wereidentified belonging to the genus Aspergillus, one isolate belong to the genus Mucor, and two other isolatescould not be identified.